Assessment of patients undergoing re-restoration after class ii amalgam - THEENATHAYALAN, MEERA; DR.MAHALAKSHMI,; S, DR.DEEPAK. (The journal of contemporary issues in business and government, 2021)
Amalgam is a restorative material especially suitable for class I and class II restoration in teeth that encounter heavy chewing forces. Amalgam restorations may also present degradation in the intra oral environment due to secondary caries, fracture and marginal breakdown and wear. The aim of the study is the number of patients undergoing re restoration after class II amalgam. It is a retrospective study. Data collection was done and entered in the excel sheet. Parameters assessed were age, gender, teeth no. and re restoration after class II amalgam. The data collection was tabulated in excel and data analysis was done using SPSS software. The association between study variables was calculated using the chi-square test. The result showed 940 individuals with re restoration after class II amalgam. The frequency was seen to be 39.2%%. The chi square test showed positive correlation between gender and amalgam restoration (P value <0.05). It may be concluded that amalgam longevity is an important issue for patients, governments and dentists to define the court of dental treatment. The re-restoration and other types of local defect increases the longevity of the amalgam restoration.